DESIGN OF AUTONOMOUS BUS USING MACHINE LEARNING AND LYAPUNOV STABILITY CONTROL - Rizaldi & Joshua Friendly Nugroho, Fahmi
According to the Regional Development Study Association study, the number of motorized vehicles in Indonesia has reached 138.5 million units at the beginning of 2018 with 87% of them being private vehicles, which caused congestion with an average time wasted on roads by 55 hours per year with 107,968 accidents in 2018. This was caused human errors of drivers, such as inability to drive or non-compliance in following traffic signs. One of the solutions to this problem is to increase the number of bus transportation services with autonomous system. To reduce the level of accidents, the autonomous system has an object detection feature that is capable of detecting objects in front of the vehicle and performing control responses quickly and precisely.